ВИЗНАЧЕННЯ ЯКІСНОГО СКЛАДУ ТА КІЛЬКІСНОГО ВМІСТУ ВУГЛЕВОДІВ У ТРАВІ ПРЕДСТАВНИКІВ РОДИНИ LAMIACEAE JUSS - Shanayda, M. I. (Фармацевтичний часопис, 2016)
DETERMINATION OF QUALITATIVE COMPOSITION AND QUANTITATIVE CONTENT OF CARBOHYDRATES IN THE HERB OF THE SPECIES BELONGING TO LAMIACEAE FAMILY M.I. Shanayda SHEI "Ternopil State Medical University by I. Ya. Horbachevsky of MPH Ukraine Introduction. Carbohydrates are an important class of natural compounds with a wide range of biological effects on the human body. Polysaccharides have broad range of biological activities: anti-inflammatory, reparative, hypolipidemic, anti-tumor, immunomodulatory and soothing effect. In this regard, the urgent task of pharmaceutical science is the search for new sources, identification of pharmacological action and expanding the practical application of plant carbohydrates. Research qualitative and quantitative composition of the carbohydrate content in the plant raw material belonging to Lamiaceae Juss. Family conducted selectively. The aim of our research was a comparative study of the carbohydrates content in the plant raw material of Lamiaceae Family representatives (Ocimum americanum L., Lophanthus anisatus Adans., Monarda fistulosa L and Satureja hortensis L.). We used the dry aboveground part of plants harvested in flowering period. Investigation methods. Quantitative determination of the total content of polysaccharides and their individual fractions conducted by gravimetric method. Monomeric carbohydrate composition was determined by thin layer chromatography and high performance liquid chromatography-mass spectrometry (determined content of free sugars). As standard samples in TLC-analysis used arabinose, galactose, glucose, xylose, rhamnose and fructose (concentration of all solutions was 1 mg / ml). The identification in HPLC-analysis was performed by retention time standard samples sugars and using mass spectra library NIST 02. Quantitative analysis was performed by adding a solution of internal standard in the test sample. As internal standard solution it was used sorbitol. Results and discussion. The comparative research of polysaccharides and sugars in the herb of 4 species belonging to Lamiaceae Family (Ocimum americanum L., Lophanthus anisatus Adans., Monarda fistulosa L. and Satureja hortensis L.) was carried out. It was determine the total content of polysaccharides and their fractions. Lophanthus anisatus has the highest total content of polysaccharides. Water-soluble polysaccharides are the dominant fractions of investigated species. The monomer composition of polysaccharide fractions was investigated by thin layer chromatography method. The content of free sugars was studied by HPLC-MS method. It was found 24 sugars in herb of Ocimum americanum (7 of them are identified), 13 - in herb of Lophanthus anisatus (5 of them are identified), 18 – in herb of Monarda fistulosa (7 of them are identified), 25 - in herb of Satureja hortensis (6 of them are identified). Fructose is the dominant component of Ocimum americanum Lophanthus anisatus and Monarda fistulos herbs, glucose and sucrose - Satureja hortensis herb. The difference between species is mainly in the quantitative content of components because qualitative component composition of sugars is quite similar. Conclusions. 1. It was carried out the comparative study of the content of polysaccharides and sugars in the aboveground part of four species belonging to Lamiaceae Family: Ocimum americanum, Lophanthus anisatus, Monarda fistulosa and Satureja hortensis. 2. It was investigated the general content of polysaccharides and their fractions. The highest total content of polysaccharides found in the herb of Lophanthus anisatus (4,46 ± 0,03), the lowest - in the herb of Monarda fistulosa (2,48 ± 0,02). 3. By thin layer chromatography and high performance liquid chromatography-mass spectrometry methods it was found from 5 to 7 sugars in herbs of investigated plants. The greatest diversity of sugars composition was identified in Monarda fistulosa and Ocimum americanum herbs. References 1. Aminokyslotnyy ta tsukrovyy sklad spyrtovoho ekstraktu z lystya shavliyi likarsʹkoyi / [O.M. Koshovyy, H.P. Zaytsev, A.M. Kovalʹova, A.M. Komisarenko] // Visnyk farmatsiyi. – 2011. - № 1 (65). – S. 49–52. 2. Burtseva O.V. Vyvchennya polisakharydnoho skladu Avena sativa L. / O.V. Burtseva, I.I. Ternynko // Visnyk farmatsiyi. – 2010. – 2(62). – S. 46–48. 3. Derzhavna Farmakopeya Ukrayiny. – 1-e vyd. Dopovnennya 3. – Kharkiv: DP «Naukovo-ekspertnyy farmakopeynyy tsentr», 2009. – 280 s. 4. Kolisnyk YU.S. Polisakharydy ta orhanichni kysloty travy hrytsykiv zvychaynykh / YU.S. Kolisnyk, V.S. Kyslychenko, V.YU. Kuznetsova // Fitoterapiya. Chasopys. – 2013. – № 1. – S. 55–58. 5. Marchyshyn S.M. Polisakharydnyy sklad travy Dracocephalum moldavica L. ta Monarda fistulosa L. / S.M. Marchyshyn, M.I. Shanayda // Materialy II Mizhnarodnoyi naukovoyi konferentsiyi «Likarsʹki roslyny: tradytsiyi ta perspektyvy doslidzhenʹ» (Berezotocha, 4-5 chervnya 2014 r.). – Lubny, 2014. – S. 174–176. 6. Olennykov N.D. Metodyka kolychestvennoho opredelenyya hruppovoho sostava uhlevodnoho kompleksa rastytelʹnykh obʺektov / D.N. Olennykov, L.M. Tankhaeva // Khymyya rast. syrʹya. – 2006. – № 4. – S. 29–33. 7. Polysakharydnyy y amynokyslotnyy sostav naybolee rasprostranennykh vydov labaznyka / M.YU. Kruhlova, D.S. Kruhlov, M.A.Khanyna,N.S.Fursa // Medytsyna y obrazovanye Sybyry. – 2011. – № 5.– s.35–38. 8. Tsurkan O.O. Fitokhimichne doslidzhennya vuhlevodnykh komponentiv shovkovytsi biloyi ta chornoyi / O.O. Tsurkan, T.V. Kovalʹchuk, O.V. Herhelʹ // Fitoterapiya. Chasopys. – 2010. – № 4. - S. 72–75. 9. Analysis of the monosaccharide composition of purified polysaccharides in Ganoderma atrum by capillary gas chromatography / Chen Y., Xie M., Wang Y. [et al.] // Phytochem. Anal. – 2009. – 20(6). – R. 503–510. 10. Isolation of a previously unidentified polysaccharide (MAR-10) from Hyssop officinalis that exhibits strong activity against Human Immunodeficiency Virus Type 1 / S. Gollapudi, H. Sharma, S. Aggarwal [et al.] // Biochem. Res. Commun. – 1995. – 210(1). – R. 145–151. 11. Li X.L. Evaluation of the antioxidant effects of polysaccharides extracted from Lycium barbarum / X.L. Li, A.G. Zhou // Med. Chem. Res. – 2007. – V. 15. – P. 471–482. 12. Rreliminary phytochemical screening of members of Lamiaceae Family / [R. Vaishali, P. Ramanath, P. Kedilaya, S. Hegde] // Int. J. Pharm. Sci. Rev. Res. – 2013. – V. 21(1). – P.131-137.